The demand for exergy during the life cycle of dwelling houses/Tipinių daugiabučių pastatų gyvavimo ciklo eksergijos poreikių įvertinimas - Martinaitis, Vytautas (Journal of Civil Engineering and Management, 1999)
The heat demand for heating and ventilation of dwelling houses depends on the climate and thermal characteristics of buildings. Energy is consumed not only in the process of maintenance of a building, but also for constructing it. The aim of current research is to assess the needs of a building life cycle (constructing, maintenance, demolition) expressed in energy units. In order to determine the energy demand of the building life cycle, lasting from a few decades to a century, the thermodynamic methodology is used. The chosen method is based on a systematic approach, applying analysis through combination of approaches such as thermodynamics exergic approach and method of an economic life cycle. The exergic method describes the energy of different types not only by its quantity, but also by the quality, ie it evaluates different forms of energy and its sources by the same quality criteria. According to the design data of four main types of blocks of flats, based on splitting the thermodynamic model into special stages and analysing data of the primary energy consumption of material processing, and the stages of it, the comparative primary energy consumption levels are defined for the principal building material production and the construction process. Primary energy consumption for typical block of flats construction material processing (forming construction goals, planning, research, coordination, designing, management of the construction process, labour force costs, service costs, transportation, use of machinery, energy and fuel consumption) is different as regards the design variations and construction work technology. For the concrete panel five-storey building it amounts to 4,42 kWh/m2, for a nine-storey building 4,36 kWh/m2, for a five-storey brick house 6,35 kWh/m2, and 11,59 kWh/m2for a nine-storey building. Regular primary energy consumption needs (maintenance and repairs) for a concrete panel five-storey building are 35,45 kWh/m2, for a nine-storey building 39,77 kWh/m2, for a five-storey brick house 44,83 kWh/m2, and 52,54 kWh/m2 for a nine-storey building. 40 per cent of the consumed energy is used for heating and ventilation, the rest of it is used for hot water preparation, lighting, home appliances and repairs. Two renovations and demolition of a building (manufacture of materials and products for renovation, research, designing, realization of the projects, demolition of the building, regeneration of the territory and the waste, systemating the data, development of a new technology) need within the building life cycle from 5 to 12 kWh/m2 of energy. In the existing blocks of flats almost three fourths of energy are used for microclimate and comfort systems, whereas heating and conditioning require one third of primary energy used within the building life cycle. The main strategy for diminishing the level of primary energy consumption in dwelling houses is aimed at developing of technical, mostly thermodynamic, features of heating systems and considering nominal power of those systems and the heating characteristics of exterior surfaces, the optimal coordination of building life cycle energy demands. Article in Lithuanian. First Published Online: 26 Jul 2012